Regulation of cleavage embryo genes upon DRP1 inhibition in mouse embryonic stem cells - Guo, Shi-Meng; Zhang, Yi-Ran; Ma, Bing-Xin; Zhou, Li-Quan; Yin, Ying (Frontiers in Cell and Developmental Biology, 2023)
Dynamic-related protein 1 (DRP1) is a key protein of mitochondrial fission. In this study, we found that inhibition of activity of DRP1, led to increased levels of cleavage embryo genes in mouse embryonic stem cells (mESCs) which might reflect a transient totipotency status derived from pluripotency. This result indicates that DRP1 inhibition in mESCs leads to a tendency to obtain a new expression profile similar to that of 2C-like state. Meanwhile, we also noticed that the downregulation of glycolysis/gluconeogenesis pathway and its related enzymes were significantly, and the key glycolytic enzymes down-regulated in in various 2C-like cells. Moreover, when DRP1 activity was inhibited from late zygote when cleavage embryo genes start to express, development of early embryos were arrested and those cleavage embryo genes failed to be efficiently silenced at late 2-cell stage. Taken together, our result shows that DRP1 plays an important role in silencing cleavage embryo genes for totipotency-to-pluripotency transition.